Pengaruh Model Pembelajaran Role Playing dengan Bantuan Video Animasi Terhadap Hasil Belajar PPKn Kelas V SD GMIT Oebobo - Patola, Dara; Ly, Petrus; Koro, Maxsel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of the role playing learning model with the help of animated videos on the learning outcomes of PPKn in grade V of GMIT Oebobo Elementary School. This study used a quantitative one group pretest-posttest method. The results of the study obtained an average pretest score of 57 and an average posttest of 80. So that student learning outcomes were better after the treatment, namely the role playing learning model assisted by animated videos. For the effect of the role playing learning model with the help of animated videos on the learning outcomes of grade V can affect learning outcomes, this is evidenced by the results of the hypothesis test, where the significance level α 0.05 with the results of > , which is 13.953 > 2.060. The magnitude of the influence of the role playing model assisted by animated videos is seen from the N-Gain Score analysis of 0.5372 which is included in the moderate increase category. So it can be concluded that is rejected and is accepted which means the role playing learning model with the help of animated videos has an effect on the learning outcomes of PPKn in grade V of GMIT Oebobo Elementary School. Keywords: Role Playing, Animated Videos, Learning Outcomes